2016
DOI: 10.1002/path.4697
|View full text |Cite
|
Sign up to set email alerts
|

TUSC3 promotes colorectal cancer progression and epithelial-mesenchymal transition (EMT) through WNT/β-catenin and MAPK signalling

Abstract: Colorectal cancer (CRC) is one of the most common malignancies and is the second leading cause of cancer death in humans. Tumour suppressor candidate 3 (TUSC3) plays an important role in embryogenesis and metabolism. Deletion of TUSC3 often causes non-syndromic mental retardation. Even though TUSC3 deregulation is frequently observed in epithelial cancers, the function of TUSC3 in CRC has remained unknown. In this study, we observed greater expression of TUSC3 at the mRNA and protein level in clinical colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 39 publications
1
93
0
Order By: Relevance
“…Inhibition of the MAPK signaling pathway blocks cell invasion in lung cancer . It also participates in CRC progression and epithelial‐to‐mesenchymal transition . Blocking this pathway thus may help treat CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the MAPK signaling pathway blocks cell invasion in lung cancer . It also participates in CRC progression and epithelial‐to‐mesenchymal transition . Blocking this pathway thus may help treat CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common human malignant neoplasm worldwide, and prognosis varies significantly between early- and late-stage diseases [1,2]. The five-year overall survival (OS) rate of stage II CRC patients is as high as 80% following surgery, but this drops to 40–60% for stage III CRC patients, who display evidence of tumor invasion and regional lymph node metastasis [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear how CBR1 regulates EMT. In this study, it was found that CBR1 suppression stimulated the intracellular signaling pathways of TGF‐β and Wnt/β‐catenin (Table ), both of which have been reported to play roles in regulating EMT . The authors speculate that CBR1 regulates EMT by interacting with the TGF‐β and Wnt/β‐catenin pathways.…”
Section: Discussionmentioning
confidence: 76%